Medieval rural settlements in the Syrian coastal region (12th and 13th centuries) - Major, Balázs, (Archaeolingua Central European archaeological heritage series ;, 2016)
This text is the result of more than a dozen years of research in the field of the hitherto unstudied medieval settlement pattern of the Syrian coastal region in the 12th and 13th centuries.